Na+/Ca2+ Exchanger 1 in Airway Smooth Muscle of Allergic Inflammation Mouse Model - Wen, Jiexia; Meng, Xiangcai; Xuan, Bin; Zhou, Tao; Gao, Heran; Dong, Hui; Wang, Yimin (Frontiers in Pharmacology, 2018)
Cytosolic free Ca2+ ([Ca2+]cyt) is essential for airway contraction, secretion and remodeling. [Ca2+]cyt homeostasis is controlled by several critical molecules, one of which is the Na+/Ca2+ exchanger 1 (NCX1) in the plasma membrane. Since little is currently known about NCX1 in the airway smooth muscle and its involvement in airway diseases, the present study was designed to investigate the expression and function of NCX1 in normal airway smooth muscle and its relevance to airway inflammation. Western blot analysis, tracheal smooth muscle contraction, and [Ca2+]cyt measurements were performed in mouse tracheal smooth muscle tissues and primary airway smooth muscle cell cultures. Additional studies were performed in a mouse model of allergic airway inflammation. Our data showed that NCX1 proteins were expressed in the human bronchial smooth muscle cells (HBSMCs), murine airway and whole lung. Carbachol raised [Ca2+]cyt in mouse tracheal smooth muscle cells and induced murine tracheal contraction, all of which were significantly attenuated by KB-R7943, a selective NCX inhibitor. Removal of extracellular Na+ increased [Ca2+]cyt in HBSMCs and mouse tracheal SMCs, which was dependent on extracellular Ca2+ and sensitive to KB-R7943. TNF-ɑ treatment of HBSMCs significantly upregulated mRNA and protein expression of NCX1 and enhanced NCX activity. Finally, KB-R7943 abolished the airway hyperresponsiveness to methacholine in an ovalbumin-induced mouse model of allergic airway inflammation. Together, these findings indicate that NCX1 in airway smooth muscle may play an important role in the development of airway hyperresponsiveness, and downregulation or inhibition of NCX1 may serve as a potential therapeutic approach for asthma.